(untitled) (Journal of the College of Basic Education, 2024)
This research aims to find out the effect of a strategy based on the theory of triune intelligence on the achievement of female first-year intermediate students in physics. To achieve this, the following null hypothesis was developed: There is no statistically significant difference at the level (0.05) between the average grades of female students in the experimental group who study according to A strategy based on the theory of tripartite intelligence and the average grades of the control group students who study the same subject in the usual way of achievement. To achieve the goal of the research, a purposive sample consisting of (66) students was selected from the moderate middle school for girls affiliated with the Second Karkh Education Directorate of Baghdad Governorate and distributed to There are two experimental and control groups, as the number of female students in the experimental group was (34) female students, and the number of female students in the control group was (32) female students. The researcher prepared the research tool represented by the achievement test, which consists of (40) multiple-choice items, and verified its validity and reliability. The researcher used a set of statistical methods, including the t-test for two independent samples and the equation of the difficulty coefficient of the items. After completing the application of the experiment and analyzing the results statistically, the researcher reached the superiority of the female students of the experimental group who studied physics according to a strategy based on the theory of triangular intelligence over the female students of the control group who They studied physics according to the usual method in the achievement test.